(untitled) (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
The present investigation deals with the glass sand potentiality of the bar sediments of Tista and Dharla rivers from different locations of Nilfamari, Lalmonirhat and Kurigram districts, Bangladesh. Accordingly, fourteen samples were selected for grain size distributions with separation of magnetic minerals. Magnetic mineral content ranges from about trace amount to 0.06 wt%. Light minerals separated by tetrabromoethane technique ranging from about 88 to 98 wt%. Moreover, glass sand as final products by flotation process evaluation ranges from 58 to 80 wt%, which indicate good quantity of glass sand. Geochemical data also suggest that glass sands are suitable for commercial grade glass owing to its SiO2 content (80.794.1 wt%). In particular, the Tista Barrage site shows high SiO2 (94.1 wt%) with reasonably low Al2O3, TiO2, and MgO+CaO percentages, which suggest an excellent glass grade quality. Unfortunately, some impurities (e.g., Fe2O3, Zr) are comparatively higher than standards, which poses difficulties making high grade glass. However, if it is possible to remove and/or decrease the major impurities, it may be used to manufacture high grade glass (colourless glass).